Laser-chemical combined machining method for metal surface micro-nano structure and metal piece
By combining ultrafast laser micro-nano processing and wet chemical treatment, the problem of micro-nano pattern/structure morphology profile regulation of metal material surfaces is solved, and efficient and flexible micro-nano structure processing on metal surfaces is achieved.
Patent Information
- Application Number
- CN202510166418.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-14
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2045-02-14
AI Technical Summary
The prior art is difficult to effectively regulate the morphological profile of the micro-nano pattern/structure of the surface of metal materials, especially in terms of processing efficiency and material type (such as metal).
Ultrafast laser micro-nano processing method is used to form the initial micro-nano structure on the surface of the metal parts, and these structures are secondaryly regulated through wet chemical treatment to achieve controllability of the morphological profile.
This method can achieve fine control of morphological profile on the metal surface, improve processing efficiency, is suitable for a variety of metal materials, and is simple to operate and low-cost.
Smart Images

Figure HDA0005272589160000011 
Figure HDA0005272589160000012 
Figure HDA0005272589160000013
Abstract
Description
Technical Field
[0001] The present application belongs to the field of ultrafast laser micro-nano processing technology, and specifically relates to a metal surface patterning micro-nano processing method and a metal part. Background Art
[0002] Ultrafast laser micro-nano processing technology uses the nonlinear interaction between ultrashort laser pulses and materials to achieve the manufacture of complex micro-nano structures and devices with high precision (up to nanometer level). It has the advantages of non-contact, strong controllability, flexible processing, and applicability to a variety of materials. It is widely used in semiconductor manufacturing, micro / nano electromechanical systems (MEMS / NEMS) manufacturing, optical component preparation, flexible electronic devices and sensor manufacturing, and functional surface preparation. However, in many cases, it is difficult to obtain the desired surface micro-nano pattern or structure by relying solely on ultrafast laser micro-nano processing, or it faces challenges such as insufficient processing efficiency. Combining ultrafast laser processing with dry etching and wet chemical treatment is an effective strategy to enhance the ability to control surface micro-nano patterns / structures and improve preparation efficiency. However, whether it is dry etching or wet chemical treatment, the materials targeted are dielectric materials such as glass and silicon or non-metallic materials. There is little research on metal materials. How to achieve the control of the morphological profile of micro-nano patterns / structures on the surface of metal materials is still a problem to be solved. Summary of the invention
[0003] The present invention aims to solve one of the technical problems in the related art at least to a certain extent. To this end, the present invention provides a processing method and a metal part that can form a patterned micro-nano structure with a controllable morphology profile on the surface of a metal part.
[0004] In the first aspect of the present application, a method for patterning metal surface micro-nano processing is provided. According to an embodiment of the present application, the method for patterning metal surface micro-nano processing includes: irradiating the surface of a metal part with an ultrafast laser according to a predetermined path to form a first micro-nano structure on the surface of the metal part; chemically treating the surface of the metal part with the first micro-nano structure with a chemical reagent to change the first micro-nano structure and form a second micro-nano structure on the surface of the metal part; cleaning the surface of the metal part after the chemical treatment to obtain a metal part with a micro-nano structure on the surface. Based on the preparation of the first micro-nano structure on the surface of the metal part by ultrafast laser micro-nano processing, the method combines wet chemical processing to perform secondary regulation on the morphology and contour of the first micro-nano structure on the surface of the metal part. The processing process is simple, efficient, free and flexible, and a micro-nano structure with controllable morphology and contour can be obtained on the surface of the metal part.
[0005] According to an embodiment of the present application, the metal part includes at least one of gold, silver, platinum, aluminum and aluminum alloys, magnesium and magnesium alloys, zinc and zinc alloys, copper and copper alloys, titanium and titanium alloys, tungsten and tungsten alloys, nickel and nickel alloys, manganese and manganese alloys, iron, and steel.
[0006] According to an embodiment of the present application, the metal piece is in the form of at least one of a metal block, a metal foil, a metal mesh, and a metal foam.
[0007] According to an embodiment of the present application, the ultrafast laser satisfies at least one of the following conditions:
[0008] The ultrafast laser is at least one of ultraviolet, infrared and visible light;
[0009] The wavelength of the ultrafast laser is 100nm to 2000nm;
[0010] The pulse width of the ultrafast laser is 1fs to 30ps;
[0011] The pulse frequency of the ultrafast laser is 1 Hz to 1 GHz;
[0012] The average power of the ultrafast laser is 1 mW to 10 kW.
[0013] According to an embodiment of the present application, the predetermined path includes at least one of a point, a parallel line, a cross line, a ring, a concentric circle, a spiral line, a zigzag line and a free pattern.
[0014] According to an embodiment of the present application, the first micro-nano structure includes a micron structure and a first nanostructure located on the first micron structure.
[0015] In some embodiments, the first micron-structure includes at least one of first micron-protrusions, first micron-depressions, and a combination thereof.
[0016] According to an embodiment of the present application, the shape of the first micron protrusion includes at least one of a conical shape, a truncated cone shape, a cylindrical shape, a square cone shape and an irregular shape protrusion.
[0017] According to an embodiment of the present application, a lateral dimension of the first micron protrusion is 0.1 μm to 1000 μm.
[0018] According to an embodiment of the present application, the shape of the first micron pits includes at least one of a circular shape, an elliptical shape, a square shape, a polygonal shape, a groove shape, and an irregular shape hole.
[0019] According to an embodiment of the present application, a lateral size of the first micron pit is 0.1 μm to 1000 μm.
[0020] According to an embodiment of the present application, the nanostructure includes at least one of nanoparticles, nanoripples, nanohairs, nanosynapses and nanoparticle clusters.
[0021] According to an embodiment of the present application, the chemical reagent includes at least one of an acid, an alkali, a salt and a mixed solution thereof, such as water, hydrochloric acid, nitric acid, sulfuric acid, hydrofluoric acid, potassium hydroxide, sodium hydroxide, sodium aluminate and a mixed solution thereof; the above chemical reagents can be used alone or mixed in a certain concentration ratio for use.
[0022] According to an embodiment of the present application, the temperature of the chemical treatment is -100°C to 300°C;
[0023] According to an embodiment of the present application, the chemical treatment time may be 1 second to 120 hours.
[0024] According to an embodiment of the present application, the change in the first micro-nano structure includes at least one of the following:
[0025] 1) The first nanostructure is removed, and the surface of the first microstructure becomes smoother;
[0026] 2) The micro cracks or micro gaps at the edge of the first micron pit profile are removed, and the edge of the first micron pit profile is clearer;
[0027] 3) The first micron protrusion gradually disappears;
[0028] 4) the profile of the first micron pit gradually expands and the depth of the first micron pit gradually increases;
[0029] 5) The shape of the first micron pit changes;
[0030] 6) Precipitates appear on the surface of the first micron protrusions or the first micron pits.
[0031] According to an embodiment of the present application, the second micro-nano structure includes at least one of a second micron protrusion, a second micron pit, and a combination thereof.
[0032] According to an embodiment of the present application, the shape of the second micron protrusion includes at least one of a conical shape, a truncated cone shape, a cylindrical shape, a square cone shape and an irregular shape protrusion.
[0033] According to an embodiment of the present application, a lateral dimension of the second micron protrusion is 0.1 μm to 1000 μm.
[0034] According to an embodiment of the present application, the shape of the second micron pits includes at least one of a circular shape, an elliptical shape, a square shape, a polygonal shape, a groove shape, and an irregular shape hole.
[0035] According to an embodiment of the present application, a lateral size of the second micron pit is 0.1 μm to 1000 μm.
[0036] In a second aspect of the present application, a metal part is provided. According to an embodiment of the present application, at least a portion of the surface of the metal part has a micro-nano structure, and the micro-nano structure is prepared by the metal surface patterning micro-nano processing method described above.
[0037] This application has at least the following advantages:
[0038] 1. In the present application, while etching the surface micro-nanostructure through wet chemical treatment, the patterned regulation of the structural contour can be achieved, breaking the limitation that wet chemical treatment can only remove specific areas on the material surface.
[0039] 2. This application can realize the etching and morphology profile control of the micro-nano structure on the metal surface, breaking the limitation of the composite method of laser micro-nano processing and chemical etching on the applied materials.
[0040] 3. The present application can achieve two-step patterning fine control of the metal surface micro-nanostructure morphology. By adjusting factors such as the processing path and process parameters of the ultrafast laser, the first-step patterning control of the surface micro-nanostructure morphology can be achieved; at the same time, by controlling factors such as the concentration and volume of chemical reagents used in the wet chemical treatment process and the temperature and time of the chemical treatment, the surface micro-nanostructure morphology can be subjected to secondary patterning control.
[0041] 4. In the present application, ultrafast laser treatment of the metal surface can increase the reaction rate in the subsequent chemical treatment process and guide the site and direction of the chemical reaction. The parallel processing characteristics of the chemical treatment improve the processing efficiency of the entire composite processing process. The entire processing process does not require special environment and process requirements, and organically combines the advantages of ultrafast laser precision processing and chemical treatment parallel processing. It is a simple, low-cost and efficient patterned micro-nano processing method for controllable morphology contours of metal surfaces. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] FIG. 1( a ) is a schematic diagram of the femtosecond laser processing path in Example 1. FIG.
[0043] FIG. 1( b ) and FIG. 1( c ) are scanning electron microscope images at different magnifications of the micro-nanostructures obtained on the surface of the aluminum alloy after femtosecond laser irradiation in Example 1.
[0044] Figures 2(a) and 2(b) show scanning electron microscope images of the micro-nano structure obtained after chemical treatment at 50°C and insulation for 10 minutes after femtosecond laser processing in Example 1 (i.e., the sample shown in Figure 1) at different magnifications. Figures 2(c), 2(d) and 2(e) are scanning electron microscope images of the micro-nano structure obtained after chemical treatment at 50°C and insulation for 30 minutes, 50 minutes and 70 minutes after femtosecond laser processing in Example 1 (i.e., the sample shown in Figure 1), respectively.
[0045] Figures 3(a), 3(b), 3(c) and 3(d) are scanning electron microscope images of the surface patterned micro-nano structures obtained after the sample processed by femtosecond laser in Example 1 was chemically treated at 50°C, kept warm for 10 min, 30 min, 50 min and 70 min respectively, and then ultrasonically cleaned with anhydrous ethanol for 10 min.
[0046] Figure 4 The sample processed by femtosecond laser in Example 1 was chemically treated at 50°C, and the curve of the roundness of the surface micron pits changes with the holding time.
[0047] Figure 5(a) is a schematic diagram of the femtosecond laser processing path in Example 2, Figures 5(b) and 5(c) are scanning electron microscope images of the micro-nanostructure obtained on the surface of the aluminum alloy after femtosecond laser irradiation in Example 2 at different magnifications; Figures 5(d) and 5(e) are scanning electron microscope images of the surface patterned micro-nanostructure obtained after the sample shown in Figure 5(b) was chemically treated at 50°C, kept warm for 60 minutes, and then ultrasonically cleaned with anhydrous ethanol for 10 minutes.
[0048] Figure 6(a) is a schematic diagram of the femtosecond laser processing path in Example 3, and Figure 6(b) is a scanning electron microscope image of the micro-nano structure obtained on the surface of the aluminum alloy after femtosecond laser irradiation in Example 3; Figures 6(c), 6(d) and 6(e) are scanning electron microscope images of the samples obtained after chemical treatment of the aluminum alloy surface at 50°C after femtosecond laser irradiation in Example 3, insulation for 10 min, 20 min and 30 min, and then ultrasonic cleaning with anhydrous ethanol for 10 min, respectively.
[0049] FIG7(a) is a schematic diagram of the femtosecond laser processing path in Example 4, and FIG7(b) is a scanning electron microscope image of the micro-nano structure obtained on the surface of the aluminum alloy after femtosecond laser irradiation in Example 4; FIG7(c), FIG7(d) and FIG7(e) are scanning electron microscope images of the surface micro-nano structure of the samples obtained after chemical treatment at 50°C and insulation for 30 min, 50 min and 70 min after femtosecond laser irradiation in Example 4, respectively, and ultrasonic cleaning with anhydrous ethanol for 10 min.
[0050] FIG8(a) is a scanning electron microscope image of the micro-nano structure obtained on the surface of the aluminum alloy after femtosecond laser irradiation in Example 5; FIG8(b), FIG8(c) and FIG8(d) are scanning electron microscope images of the surface micro-nano structure of the samples obtained after chemical treatment at 50°C and insulation for 30 min, 50 min and 70 min after femtosecond laser irradiation in Example 5, respectively, and ultrasonic cleaning with anhydrous ethanol for 10 min.
[0051] Figure 9(a) is a schematic diagram of the femtosecond laser processing path in Example 6, and Figure 9(b) is a scanning electron microscope image of the micro-nano structure obtained on the surface of the aluminum alloy after femtosecond laser irradiation in Example 6; Figure 9(c) is a scanning electron microscope image of the surface micro-nano structure after the aluminum alloy surface was chemically treated twice at 50°C and ultrasonically cleaned with anhydrous ethanol for 10 minutes after femtosecond laser irradiation in Example 6. The figures show the microscopic morphology of different positions on the same sample surface from left to right.
[0052] Figure 10(a) is a schematic diagram of the femtosecond laser processing path in Example 7, and Figure 10(b) is a scanning electron microscope image of the micro-nano structure obtained on the surface of the aluminum alloy after femtosecond laser irradiation in Example 7; Figure 10(c) is a scanning electron microscope image of the surface micro-nano structure after the aluminum alloy surface was chemically treated twice at 50°C and ultrasonically cleaned with anhydrous ethanol for 10 minutes after femtosecond laser irradiation in Example 7. The figures show the microscopic morphology of different positions on the same sample surface from left to right. DETAILED DESCRIPTION
[0053] Embodiments of the present invention are described in detail below, and examples of the embodiments are shown in the accompanying drawings. The embodiments described below with reference to the accompanying drawings are exemplary and intended to be used to explain the present invention, but should not be understood as limiting the present invention.
[0054] In a first aspect of the present application, a metal surface patterning micro-nano processing method is provided. According to an embodiment of the present application, the metal surface patterning micro-nano processing method comprises the following steps:
[0055] S10: irradiating the surface of the metal part with an ultrafast laser according to a predetermined path to form a first micro-nano structure on the surface of the metal part.
[0056] According to the embodiments of the present application, the specific material of the metal part is not particularly limited, and can be a metal or alloy, such as at least one of gold, silver, platinum, aluminum and aluminum alloys, magnesium and magnesium alloys, zinc and zinc alloys, copper and copper alloys, titanium and titanium alloys, tungsten and tungsten alloys, nickel and nickel alloys, manganese and manganese alloys, iron, and steel, and the specific grades of the above metals or alloys are not limited. In some specific embodiments, the metal part can be an aluminum alloy part. As an example, the aluminum alloy part includes at least one of 1XXX series, 2XXX series, 3XXX series, 4XXX series, 5XXX series, 6XXX series, 7XXX series, and 8XXX series aluminum alloy parts, and the specific grades are not limited. As a result, the processing method has a wide range of applications, and can be used for micro-nano structure processing on a variety of metal surfaces, suitable for a variety of purposes and usage scenarios.
[0057] According to the embodiments of the present application, the form of the metal part is not particularly limited, and it can be at least one of a metal block, a metal foil, a metal mesh or a metal foam; the shape of the metal part is also not particularly limited, and it can be any regular or irregular shape. In some embodiments, the metal part includes at least one of a metal block and a metal foil. Thus, it can be applied to the use requirements of various metal parts. It can be understood that the metal part can also be various structural parts, which have the necessary structure and shape of the corresponding structural parts, and will not be described in detail here.
[0058] According to the embodiments of the present application, the size and thickness of the metal piece are not limited. In some embodiments, the thickness of the metal piece is 0.01 to 100 mm. Therefore, the application range is wide and can meet the use requirements of different scenarios.
[0059] It is understandable that before ultrafast laser irradiation, the metal parts can be pretreated to remove contaminants on the surface of the metal parts. Specifically, the surface of the metal parts can be ground and polished or the metal parts can be placed in a solvent (such as anhydrous ethanol or acetone, etc.) for ultrasonic cleaning and then taken out, dried naturally at room temperature, or blown dry with dry gas to remove surface contaminants. As an example, the metal parts can be ultrasonically cleaned in anhydrous ethanol or acetone for 1 to 120 minutes; the gas used to blow dry the surface of the metal parts is compressed air, nitrogen or argon, the air pressure can be set to 1 to 200 bar, and the blowing time can be 1 to 300 seconds.
[0060] In some embodiments, the ultrafast laser irradiation can be performed using an ultrafast laser processing system. Specifically, the metal part can be placed on a processing platform of the ultrafast laser processing system, and the ultrafast laser can be irradiated on the surface of the metal part and scanned according to a pre-set processing path, so as to obtain a patterned first micro-nano structure on the surface of the metal part.
[0061] In some embodiments, the ultrafast laser processing system may include an ultrafast laser, an external optical path system, a motion system, an observation system, a gas protection system, a dust removal system, etc.; the scanning processing of the ultrafast laser on the surface of the metal part can be achieved through a scanning galvanometer (which can be a two-dimensional scanning galvanometer, a three-dimensional scanning galvanometer, a dynamic focusing galvanometer, etc.), a polygonal rotating mirror, a multi-beam interference unit, a spatial light modulator, a diffraction optical unit or a CNC translation stage (which can be an XY two-axis translation stage, an XYZ three-axis translation stage, a multi-axis translation stage, etc.) or an industrial robot. The scanning processing of more complex paths and more delicate structures can also be achieved through the cooperation of a scanning galvanometer, a polygonal rotating mirror, a multi-beam interference unit, a spatial light modulator, a diffraction optical unit and a translation stage or a robot. In the scanning processing, the relative motion speed of the laser and the metal surface can be 0.01 to 100000 mm / s, the scanning interval can be 1 to 1000 μm, and the number of repeated processing times can be 1 to 1000 times.
[0062] It can be understood that ultrafast laser refers to lasers with pulse widths in the range of picoseconds (ps) to femtoseconds (fs). The pulses of these lasers are very short and can be used for precise processing and measurement of materials with extremely high time resolution.
[0063] According to an embodiment of the present application, the ultrafast laser is at least one of ultraviolet, infrared and visible light.
[0064] According to an embodiment of the present application, the wavelength of the ultrafast laser is 100nm to 2000nm, such as 193nm, 206nm, 213nm, 248nm, 258nm, 266nm, 308nm, 337nm, 343nm, 345nm, 355nm, 390nm, 400nm, 445nm, 488nm, 514nm, 515nm, 517nm, 532nm, 633nm, 655nm, 658nm, 780nm, 800nm, 810nm, 900nm, 920nm, 940nm, 980nm, 1030nm, 1035nm, 1064nm, 1315nm, 1470nm, 1500nm, 1550nm, 2000nm, etc.
[0065] According to an embodiment of the present application, the pulse width of the ultrafast laser is 1fs to 30ps, such as 1fs, 10fs, 50fs, 100fs, 150fs, 190fs, 200fs, 220fs, 240fs, 250fs, 260fs, 280fs, 300fs, 350fs, 400fs, 500fs, 800fs, 1ps, 2ps, 3ps, 4ps, 5ps, 6ps, 7ps, 8ps, 9ps, 10ps, 11ps, 12ps, 15ps, 20ps, 25ps, 30ps, etc.
[0066] According to an embodiment of the present application, the pulse frequency of the ultrafast laser is 1 Hz to 1 GHz, such as 1 Hz, 10 Hz, 100 Hz, 1 kHz, 10 kHz, 20 kHz, 25 kHz, 30 kHz, 40 kHz, 50 kHz, 100 kHz, 110 kHz, 150 kHz, 200 kHz, 220 kHz, 250 kHz, 300 kHz, 330 kHz, 350 kHz, 400 kHz, 450 kHz, 500 kHz, 550 kHz, 600 kHz, 650 kHz, 700 kHz, 750kHz, 800kHz, 850kHz, 900kHz, 950kHz, 1MHz, 2MHz, 3MHz, 4MHz, 5MHz, 6MHz, 7MHz, 8MHz, 9MHz, 10MHz, 20MHz, 30MHz, 40M Hz, 50MHz, 60MHz, 70MHz, 80MHz, 90MHz, 100MHz, 200MHz, 300MHz, 400MHz, 500MHz, 600MHz, 700MHz, 800MHz, 900MHz, 1GHz, etc.
[0067] According to an embodiment of the present application, the average power of the ultrafast laser is 1 mW to 10 kW, such as 1 mW, 10 mW, 100 mW, 500 mW, 1 W, 2 W, 3 W, 4 W, 5 W, 6 W, 7 W, 8 W, 9 W, 10 W, 20 W, 30 W, 40 W, 50 W, 60 W, 70 W, 80 W, 90 W, 100 W, 200 W, 500 W, 1 kW, etc.
[0068] Ultrafast laser meets the above conditions and can quickly and effectively form the first micro-nano structure on the surface of the metal part. By adjusting the above parameters of the ultrafast laser, the first micro-nano structure of different shapes, sizes and distributions can be obtained. The morphology-controllable micro-nano structure can be obtained according to different application scenarios and needs to meet different usage needs.
[0069] It can be understood that in this step, the first micro-nano structure is formed on the surface of the metal part by scanning the ultrafast laser along a predetermined path on the surface of the metal part. Specifically, the high-energy laser can ablate the metal part to form the first micro-nano structure on the surface of the metal part. By selecting different scanning paths, a variety of patterned first micro-nano structures can be formed on the surface of the metal part.
[0070] According to an embodiment of the present application, the predetermined path includes at least one of a point, a parallel line, a cross line, a ring, a concentric circle, a spiral line, a zigzag line, and a free pattern. As an example, if the predetermined path is a point, a pit can be formed at the ultrafast laser irradiation position; if the predetermined path is a parallel line, multiple pits distributed along the parallel lines or grooves along the parallel lines may be formed by adjusting the parameters of the ultrafast laser. In summary, the metal part at the position irradiated by the ultrafast laser is ablated to form a depression, and protrusions are correspondingly formed between adjacent depressions. By irradiating the ultrafast laser along different paths, a first micro-nano structure with diversified patterns can be formed.
[0071] Furthermore, the parameters of the ultrafast laser also have an important influence on the first micro-nano structure formed. For example, different pulse widths, pulse frequencies, scanning speeds during ultrafast laser irradiation, etc. may form first micro-nano structures with different patterns even when irradiated along the same path. For example, when the pulse frequency is constant, if the scanning speed is fast, multiple spaced pits may be formed along the irradiation path, while if the scanning speed is slow, continuous grooves may be formed along the irradiation path. Based on similar principles, other ultrafast laser parameters also affect the pattern shape of the first micro-nano structure, and thus, by adjusting the relevant parameters of the ultrafast laser, a rich variety of patterned first micro-nano structures can be obtained.
[0072] Herein, micro-nano structures refer to structures at the microscopic scale (micrometer level) and nanometer scale, and these structures usually have at least one dimension at the micrometer or nanometer level.
[0073] According to an embodiment of the present application, the first micro-nano structure includes a first micron structure and a first nano structure located on the first micron structure.
[0074] In some embodiments, the first micron-structure includes at least one of first micron-protrusions, first micron-depressions, and a combination thereof.
[0075] According to an embodiment of the present application, the shape of the first micron protrusion includes at least one of a conical shape, a truncated cone shape, a cylindrical shape, a square cone shape and an irregular shape protrusion.
[0076] According to an embodiment of the present application, the lateral size of the first micron protrusion is 0.1 μm to 1000 μm, specifically 0.1 μm, 0.2 μm, 0.5 μm, 1 μm, 5 μm, 10 μm, 20 μm, 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm, 150 μm, 200 μm, 250 μm, 300 μm, 350 μm, 400 μm, 450 μm, 500 μm, 750 μm, 1000 μm, etc. It should be noted that the lateral size of the first micron protrusion refers to the width of the micron protrusion in the horizontal direction.
[0077] According to an embodiment of the present application, the shape of the first micron pits includes at least one of a circular shape, an elliptical shape, a square shape, a polygonal shape, a groove shape, and an irregular shape hole.
[0078] According to an embodiment of the present application, the lateral size of the first micron pit is 0.1 μm to 1000 μm, specifically 0.1 μm, 0.2 μm, 0.5 μm, 1 μm, 5 μm, 10 μm, 20 μm, 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm, 150 μm, 200 μm, 250 μm, 300 μm, 350 μm, 400 μm, 450 μm, 500 μm, 750 μm, 1000 μm, etc. It should be noted that the lateral size of the first micron pit refers to the width of the micron pit in the horizontal direction.
[0079] According to the embodiments of the present application, the arrangement of the first micron pits and the first micron protrusions is not particularly limited and can be adjusted according to the predetermined path of the ultrafast laser, for example, it can be arranged regularly or randomly. As an example, a plurality of first micron pits and / or a plurality of first micron protrusions can be arranged at intervals along a certain direction, and the size of the plurality of first micron pits and / or a plurality of first micron protrusions, the spacing between adjacent first micron pits or adjacent first micron protrusions, etc. can be flexibly adjusted by adjusting the parameters of the ultrafast laser.
[0080] According to an embodiment of the present application, the first nanostructure includes at least one of nanoparticles, nanoripples, nanohair, nanosynapses and nanoparticle clusters. Specifically, the first nanostructure is that under ultrafast laser irradiation, an extreme non-equilibrium state is generated on the surface of the metal part, resulting in complex physical processes such as melting, evaporation, ablation, Coulomb explosion, phase explosion, etc. on the surface of the metal part, thereby generating a nanostructure on the surface of the metal part. The first nanostructure can be nanoparticles, nanoripples, nanohair, nanosynapses or nanoparticle clusters.
[0081] It can be understood that in this step, first micron structures and first nanostructures of different shapes, sizes, and arrangements can be formed on the surface of the metal part. As an example, a plurality of first micron pits arranged in a matrix, a plurality of first micron pits arranged along concentric rings, annular grooves arranged in a matrix, a plurality of first micron protrusions arranged in a matrix, etc. can be formed. Furthermore, the spacing and size between the plurality of first micron pits, first micron protrusions, and grooves can be gradually changed in a certain direction (such as gradually increasing or decreasing), etc. Further, the first micron structure can have at least one first nanostructure of nanoparticles, nanoripples, nanohair, nanosynapses, and nanoparticle clusters.
[0082] S20: using a chemical reagent to chemically treat the surface of the metal part having the first micro-nano structure formed thereon, so that the first micro-nano structure changes and a second micro-nano structure is formed on the surface of the metal part.
[0083] In this step, the chemical reagent can further etch the metal part. The chemical treatment of the chemical reagent can further shape and tune the first micro-nano structure, and accelerate the processing rate. That is, the first micro-nano structure further changes during the chemical treatment, so that the second micro-nano structure with the target contour and morphology is quickly obtained on the surface of the metal part.
[0084] Specifically, part or all of the metal part can be immersed in a chemical reagent for chemical treatment, or the chemical reagent can be dripped onto the surface of the metal part for chemical treatment. The specific selection can be flexibly made according to actual conditions, and the present application has no particular limitations.
[0085] In some embodiments, the chemical treatment can be performed once or multiple times, that is, the metal part can be immersed in a chemical reagent for a certain period of time to complete the chemical treatment; or a certain volume of chemical reagent can be dripped onto the surface of the metal part and kept for a certain period of time to complete the chemical treatment; the metal part can also be immersed in a chemical reagent for a certain period of time and then taken out, and then immersed in a new chemical reagent for a certain period of time. The chemical reagent can be replaced multiple times as needed to complete the chemical treatment; a certain volume of chemical reagent can also be dripped onto the surface of the metal part and kept for a certain period of time, the chemical reagent on the surface of the metal part can be removed, and then a new chemical reagent can be dripped again. Of course, multiple chemical reagent renewal operations can also be performed according to actual needs to complete the chemical treatment. Specifically, after replacing the new chemical reagent, the reaction rate can be accelerated. According to the actual situation, whether to perform the chemical treatment once or multiple times can be selected, which can take into account the controllable contour morphology and processing rate of the micro-nano structure.
[0086] According to an embodiment of the present application, the change in the first micro-nano structure includes at least one of the following:
[0087] 1) The first nanostructure is removed, and the surface of the first microstructure becomes smoother;
[0088] 2) The micro cracks or micro gaps on the edge of the first micron pit contour are removed, and the contour edge is clearer;
[0089] 3) The first micron protrusion gradually disappears;
[0090] 4) the profile of the first micron pit gradually expands and the depth of the first micron pit gradually increases;
[0091] 5) The shape of the first micron pit changes;
[0092] 6) Precipitates appear on the surface of the first micron protrusions or the first micron pits.
[0093] Specifically, during the chemical treatment process, which is the process of chemical reagents reacting with the surface of the metal part, or the process of chemical reagents corroding the metal part, the first nanostructure and the first microstructure in the first micro-nano structure can be corroded, so that the first nanostructure can gradually disappear, and as the first microstructure is corroded, the surface of the first microstructure can gradually become smoother; as the corrosion proceeds, the microcracks or microcracks existing at the edge of the first micron pit contour can also be removed, and the edge of the first micron pit contour gradually becomes clearer; and the size of the first micron pit can gradually expand, and the depth can also gradually deepen; and when the first microstructure includes a first micron protrusion, as the corrosion progresses, the size of the first micron protrusion decreases, or the first micron protrusion gradually disappears. As an example, the change in the shape of the first micron pit can be manifested as a gradual transition from an irregular elliptical pit to a perfect circular pit and finally presenting a polygonal contour.
[0094] It should be noted that when the chemical treatment is carried out to a certain extent, as the corrosion reaction proceeds, the composition of the chemical reagent also changes, and the components in the chemical reagent will precipitate to form precipitates. Specifically, according to the different shapes and structures of the first micro-nano structure, as well as the composition of the precipitate, the precipitate may present different structures and shapes. For example, when the first micro-nano structure is a pit, the precipitate can be presented in the form of a shell at the bottom of the pit. When the first micro-nano structure is a protrusion, the precipitate can be presented in the form of rod-shaped crystals or nano-hair. Because there is no chemical bond or other binding force connection between the precipitate and the first micro-nano structure, it can be removed in the subsequent cleaning step and does not affect the morphology of the second micro-nano structure. As an example, the precipitate with shell-like structural characteristics is usually conical or irregular in shape, generally appears at the bottom of the first micron pit, and its thickness can be 0.01 to 100 μm; the rod-shaped crystals can appear on the surface of the first micron pit and / or the first micron protrusion, and its diameter can be 0.01 to 100 μm, and its length can be 0.01 to 100 μm; and the nanohair can be closely distributed on the surface of the first micron pit and / or the first micron protrusion, and the length of the nanohair is about 1 nm to 100 μm.
[0095] According to the embodiments of the present application, it is necessary to select chemical reagents that can react with metal parts according to the types of metal parts, and the reaction speed with the metal parts can be controlled by adjusting the concentration, ratio and volume of the chemical reagents, thereby better adjusting the morphology of the micro-nano structure.
[0096] According to the embodiments of the present application, the chemical reagents that can be used include at least one of acids, bases, salts and mixed solutions thereof, such as water, hydrochloric acid, nitric acid, sulfuric acid, hydrofluoric acid, potassium hydroxide, sodium hydroxide, sodium aluminate, etc. The above chemical reagents can be used alone or mixed in a certain concentration ratio.
[0097] As an example, the chemical reagent includes a mixed aqueous solution of sodium hydroxide with a molar concentration of 0.01 mol / L to 10.0 mol / L and sodium aluminate with a molar concentration of 0.01 mol / L to 10.0 mol / L. The chemical reagent with the above composition and concentration can react with the aluminum alloy part, and the reaction rate is controllable, thereby better regulating the first micro-nano structure to obtain a metal part with a target micro-nano structure.
[0098] In some embodiments, the molar concentration of sodium hydroxide can be 0.03-0.06 mol / L, 0.09-1.5 mol / L; more specifically, it can be 0.01 mol / L, 0.03 mol / L, 0.05 mol / L, 0.06 mol / L, 0.09 mol / L, 0.1 mol / L, 0.2 mol / L, 0.3 mol / L, 0.4 mol / L, 0.5 mol / L, 0.6 mol / L, 0.7 mol / L, 0.8 mol / L, 0.9 mol / L, 1 mol / L, 2 mol / L, 3 mol / L, 4 mol / L, 5 mol / L, 6 mol / L, 7 mol / L, 8 mol / L, 9 mol / L, 10 mol / L. / L, etc.; the molar concentration of sodium aluminate can be 0.03-0.06mol / L, 0.09-1.5mol / L; more specifically, it can be 0.01mol / L, 0.03mol / L, 0.05mol / L, 0.06mol / L, 0.09mol / L, 0.1mol / L, 0.2mol / L, 0.3mol / L, 0.4mol / L, 0.5mol / L, 0.6mol / L, 0.7mol / L, 0.8mol / L, 0.9mol / L, 1mol / L, 2mol / L, 3mol / L, 4mol / L, 5mol / L, 6mol / L, 7mol / L, 8mol / L, 9mol / L, 10mol / L, etc.
[0099] According to the embodiments of the present application, the temperature of the chemical treatment is -100°C to 300°C, such as 25°C to 60°C, and more specifically 0°C, 10°C, 20°C, 25°C, 30°C, 40°C, 50°C, 60°C, 70°C, 80°C, 90°C, 100°C, 120°C, 150°C, 180°C, 200°C, 250°C, etc. Within the above temperature range, the reaction rate of the chemical reagent and the metal part is fast, the processing efficiency is high, and the reaction rate is well controllable, and the first micro-nano structure is accurately adjusted to obtain a second micro-nano structure with controllable morphology.
[0100] According to the embodiments of the present application, the time of the chemical treatment may be 1s to 120h, such as 10min to 120min, more specifically 1s, 30s, 1min, 10min, 15min, 20min, 30min, 40min, 50min, 60min, 70min, 80min, 90min, 100min, 2h, 5h, 10h, 20h, 30h, 40h, 50h, 60h, 70h, 80h, 90h, 100h, 120h, etc. It can be understood that as the reaction time is longer, the control range of the first micro-nano structure is larger, and within the above time range, a variety of second micro-nano structures can be realized to meet the use requirements of different scenarios.
[0101] It is understood that by combining ultrafast laser irradiation and chemical treatment, a second micro-nano structure with diversified patterns can be obtained, which can be flexibly adjusted according to actual use requirements. In some embodiments, the second micro-nano structure includes at least one of a second micron protrusion, a second micron pit, and a combination thereof.
[0102] According to an embodiment of the present application, the shape of the second micron protrusion includes at least one of a conical shape, a truncated cone shape, a cylindrical shape, a square cone shape and an irregular shape protrusion.
[0103] According to an embodiment of the present application, the lateral size of the second micron protrusion is 0.1μm to 1000μm, such as 0.1μm, 0.2μm, 0.5μm, 1μm, 5μm, 10μm, 20μm, 30μm, 40μm, 50μm, 60μm, 70μm, 80μm, 90μm, 100μm, 150μm, 200μm, 250μm, 300μm, 350μm, 400μm, 450μm, 500μm, 750μm, 1000μm, etc.
[0104] According to an embodiment of the present application, the shape of the second micron pits includes at least one of a circular shape, an elliptical shape, a square shape, a polygonal shape, a groove shape, and an irregular shape hole.
[0105] According to an embodiment of the present application, the lateral size of the second micron pit is 0.1μm to 1000μm, such as 0.1μm, 0.2μm, 0.5μm, 1μm, 5μm, 10μm, 20μm, 30μm, 40μm, 50μm, 60μm, 70μm, 80μm, 90μm, 100μm, 150μm, 200μm, 250μm, 300μm, 350μm, 400μm, 450μm, 500μm, 750μm, 1000μm, etc.
[0106] S30: Cleaning the surface of the metal part after the chemical treatment to obtain a metal part with a micro-nano structure on the surface.
[0107] In this step, chemical reagents and precipitates on the surface of the metal parts can be removed by cleaning.
[0108] Specifically, there is no particular limitation on the specific method of cleaning, as long as the chemical reagents and precipitates on the surface of the metal part can be effectively removed. As an example, ultrasonic cleaning can be performed. Specifically, the chemically treated metal part can be placed in anhydrous ethanol or acetone for ultrasonic cleaning, and then taken out from the anhydrous ethanol or acetone after cleaning, and then dried naturally at room temperature or blown dry with dry gas.
[0109] As an example, the chemically treated metal parts can be ultrasonically cleaned in anhydrous ethanol or acetone for 1 min to 120 min, and the gas used to blow dry the surface of the metal parts is compressed air, nitrogen or argon. The air pressure can be set to 1 bar to 200 bar, and the blowing time can be 1 s to 300 s.
[0110] This method uses ultrafast laser micro-nano processing to prepare the first micro-nano structure on the surface of the metal part, and combines wet chemical treatment to perform secondary regulation on the morphology and contour of the first micro-nano structure on the surface of the metal part. The processing process is simple, efficient, free and flexible, and a micro-nano structure with controllable morphology and contour can be obtained on the surface of the metal part.
[0111] In the second aspect of the present application, a metal part is provided. According to an embodiment of the present application, at least a portion of the surface of the metal part has a micro-nano pattern and / or structure, and the micro-nano pattern and / or structure is prepared by the processing method described above. The metal part can adjust the surface micro-nano structure profile and morphology as needed, and is suitable for a variety of use scenarios such as semiconductor manufacturing, micro / nano electromechanical system (MEMS / NEMS) manufacturing, optical component preparation, flexible electronic device and sensor manufacturing, functional surface preparation and biomedical engineering.
[0112] The embodiments of the present application are described in detail below.
[0113] Example 1
[0114] This embodiment regulates the profile of large-pitch micron pits on the surface of 6061 aluminum alloy, including the following steps:
[0115] (1) The aluminum alloy sample to be processed was placed in anhydrous ethanol for ultrasonic cleaning for 10 minutes, then taken out and blown dry with dry nitrogen to remove surface contaminants.
[0116] (2) Femtosecond laser was used for surface processing, with a central wavelength of 343nm, a pulse width of 500fs, and a pulse repetition frequency of 330kHz. The area of the aluminum alloy sample used was 3×3mm 2 , with a thickness of 0.22 mm. The parameters used for femtosecond laser processing are: average power 15 W, scanning speed 500 mm / s, and scanning times 10 times. The laser processing path is a 60° close-packed array with three concentric rings as units. The diameters of the concentric rings from the outside to the inside are 50 μm, 35 μm, and 15 μm, respectively. The edge spacing of adjacent concentric ring units is 23 μm. The schematic diagram of the processing path is shown in Figure 1(a).
[0117] Figure 1(b) and Figure 1(c) are scanning electron microscope images of the micro-nanostructures obtained on the surface of the aluminum alloy after femtosecond laser irradiation at different magnifications. As shown in the figure, the micron pit structure obtained after femtosecond laser irradiation is regularly arranged, and the pits present an irregular elliptical shape, with a lateral size of about 35 to 50 μm, a depth of about 40 μm, and a pit spacing of about 35 to 40 μm; the edges of the micron pits are densely covered with nanoparticles and their cluster structures, with a size of about 500 nm to 3 μm; in addition, microcracks or microgap-like features can be seen on the edges of the micron pits, and the pit edges are relatively rough.
[0118] (3) Prepare four 50 ml portions of a mixed solution of sodium hydroxide and sodium aluminate with a molar concentration of 30 mol / L each in a beaker, place the samples processed by laser in step (2) into the four beakers containing the mixed solution respectively, and then place the beakers in a heating furnace, set the heating temperature to 50° C., and set the insulation time of the four beakers to 10 min, 30 min, 50 min and 70 min, respectively.
[0119] FIG2(a) and FIG2(b) show scanning electron microscope images of the sample processed by femtosecond laser at different magnifications after chemical treatment at 50°C for 10 minutes in step (3), and FIG2(c), FIG2(d) and FIG2(e) are scanning electron microscope images of the micro-nanostructure obtained after chemical treatment for 30 minutes, 50 minutes and 70 minutes in step (3), respectively. As can be seen from FIG2(a) and FIG2(b), after chemical treatment at 50°C for 10 minutes, the nanoparticles and their cluster structures on the surface of the micron pits in step (2) are significantly removed, and at the same time, the microcracks or micro-gap features on the edge and inner wall of the micron pits disappear, the edge of the micron pits becomes sharper and smoother, the outline of the micron pits becomes clearer, and the size of the micron pits increases, wherein the lateral size increases to about 50-55 μm, the pit spacing decreases to about 18-23 μm, and the outline of the micron pits transitions from the irregular ellipse before chemical treatment to a perfect circle. As can be seen from Figure 2(c) and Figure 2(d), after chemical treatment at 50℃ for 30min and 50min, the size of the micron pits further expanded. After chemical treatment for 50min, the lateral size of the micron pits increased to about 60-65μm, the pit spacing decreased to about 8-13μm, and shell-like precipitates appeared at the bottom of the pits. The height of the shell-like precipitates gradually increased with the increase of the holding time of the chemical treatment. When the holding time was 50min, the height of the shell-like precipitates was about 5-10μm and the thickness was about 1-3μm. As can be seen from Figure 2(e), after chemical treatment at 50℃ for 70min, the contour of the micron pits was close to a perfect circle, the lateral size of the pits increased to about 65-70μm, the pit spacing further decreased to about 3-8μm, and the adjacent pits almost merged. At the same time, rod-like crystals are further precipitated on the surface of the shell-like structure precipitates in the micron pits. The diameter of the rod-like crystals is about 0.5 to 3 μm, and the length of the rod-like crystals is about 0.5 to 5 μm. The surface of the micron pit structure is covered with densely distributed nano-hairs, and the length of the nano-hairs is about 200 to 500 nm.
[0120] (4) The sample obtained by the chemical treatment in step (3) is placed in anhydrous ethanol and ultrasonically cleaned for 10 minutes, then taken out and naturally dried at room temperature.
[0121] Figure 3(a) to Figure 3(d) The following are scanning electron microscope images of the surface patterned micro-nano structures of the samples subjected to the chemical treatment at 50° C. for 10 min, 30 min, 50 min and 70 min in step (3) after ultrasonic cleaning in step (4). It can be seen from the figure that after ultrasonic cleaning, the shell-like structure precipitates in the micron pits found in step (3), the rod-like crystals precipitated on the surface of the shell-like structure precipitates, and the dense nano-hair covering the surface of the micron pits have all been removed.
[0122] Figure 4 is the roundness (R) of the micron pits obtained by femtosecond laser processing in step (2) max / R min ) with the change curve of the chemical treatment insulation time (Time) in step (3). As can be seen from the figure, with the increase of the chemical treatment insulation time, the long axis R of the elliptical pit max With short axis R min The ratio gradually approaches 1, that is, its shape contour gradually changes from the original irregular ellipse to a perfect circle, realizing the regulation of the morphology contour of the patterned micro-nanostructure on the surface of the aluminum alloy.
[0123] Example 2
[0124] This embodiment regulates the profile of small-pitch micron pits on the surface of 6061 aluminum alloy, including the following steps:
[0125] (1) The aluminum alloy sample to be processed was placed in anhydrous ethanol for ultrasonic cleaning for 10 minutes, then taken out and blown dry with dry nitrogen to remove surface contaminants.
[0126] (2) Femtosecond laser was used for surface processing, with a central wavelength of 343nm, a pulse width of 500fs, and a pulse repetition frequency of 330kHz. The area of the aluminum alloy sample used was 3×3mm 2 , with a thickness of 0.22 mm. The parameters used for femtosecond laser processing are: average power 15 W, scanning speed 500 mm / s, and scanning times 10 times. The laser processing path is a 60° close-packed array with three concentric rings as units. The diameters of the concentric rings from the outside to the inside are 50 μm, 35 μm, and 15 μm, respectively. The edge spacing of adjacent concentric ring units is 5 μm. The schematic diagram of the processing path is shown in Figure 5(a).
[0127] Figures 5(b) and 5(c) are scanning electron microscope images of the micro-nanostructures obtained on the surface of the aluminum alloy after femtosecond laser irradiation at different magnifications. As shown in the figure, the micron pit structure obtained after femtosecond laser irradiation is regularly arranged, and the pits present an irregular elliptical shape, with a lateral size of about 35 to 50 μm, a depth of about 40 μm, and a pit spacing of about 15 to 20 μm; the edges of the micron pits are densely covered with nanoparticles and their cluster structures, with a size of about 500 nm to 3 μm; in addition, microcracks or micro-gap features can be seen on the edges of the micron pits, and the pit edges are relatively rough.
[0128] (3) Use a beaker to prepare 50 ml of a mixed solution of sodium hydroxide and sodium aluminate with a molar concentration of 30 mol / L each, place the sample processed by laser in step (2) into the beaker containing the mixed solution, and then place the beaker in a heating furnace, set the heating temperature to 50° C., and set the insulation time to 60 min.
[0129] (4) The sample obtained by the chemical treatment in step (3) is placed in anhydrous ethanol and ultrasonically cleaned for 10 minutes, then taken out and naturally dried at room temperature.
[0130] Figures 5(d) and 5(e) show scanning electron microscope images of the surface micro-nanostructure obtained after the micron pits obtained by femtosecond laser processing in step (2) are chemically treated in step (3) and ultrasonically cleaned in step (4) at different magnifications. As can be seen from the figure, the micron pits obtained by femtosecond laser processing have expanded to a closely interconnected state after chemical treatment for 60 minutes and ultrasonic cleaning, and the shape of the pits has changed from an irregular ellipse to a nearly hexagonal honeycomb. The nanoparticles and their cluster structures on the surface of the micron pits in step (2) are significantly removed, and the microcracks or micro-gap features on the edge and inner wall of the micron pits disappear, the edge of the micron pits is sharper and smoother, and the outline of the micron pits is clearer.
[0131] Example 3
[0132] This embodiment regulates the micron-protrusion morphology profile on the surface of 6061 aluminum alloy, including the following steps:
[0133] (1) The aluminum alloy sample to be processed was placed in anhydrous ethanol for ultrasonic cleaning for 10 minutes, then taken out and blown dry with dry nitrogen to remove surface contaminants.
[0134] (2) Femtosecond laser was used for surface processing, with a central wavelength of 343 nm, a pulse width of 500 fs, a pulse repetition frequency of 330 kHz, and an area of 3 × 3 mm2 for the aluminum alloy sample used. 2 , thickness is 0.22mm.
[0135] The parameters used for femtosecond laser processing are: average power 14 W, scanning speed 500 mm / s, and scanning times 15 times. The laser processing path is a vertical cross line with a spacing of 25 μm between adjacent lines. The schematic diagram of the processing path is shown in Figure 6(a).
[0136] Figure 6(b) is a scanning electron microscope image of the micro-nanostructure obtained on the surface of the aluminum alloy after femtosecond laser irradiation. As shown in the figure, the micro-protrusion structure obtained after femtosecond laser irradiation is regularly arranged, with a lateral size of about 20 to 25 μm and a height of about 35 μm. The surface of the micro-protrusion is densely covered with nanoparticles and their cluster structures, with a size of about 200 nm to 3 μm.
[0137] (3) Prepare three 50 ml portions of a mixed solution of sodium hydroxide and sodium aluminate with a molar concentration of 30 mol / L each in a beaker, place the samples processed by laser in step (2) into the three beakers containing the mixed solution respectively, and then place the beakers in a heating furnace, set the heating temperature to 50° C., and set the insulation time of the three beakers to 10 min, 20 min, and 30 min, respectively.
[0138] Figure 6(c) to Figure 6(e) The figures show the scanning electron microscope images of the surface micro-nanostructures of the micron protrusions obtained by the femtosecond laser processing in step (2) after the chemical treatment in step (3) for 10 minutes, 20 minutes and 30 minutes, respectively. It can be seen from the figure that after the micron protrusions obtained by the femtosecond laser processing were chemically treated for 10 minutes, the nanoparticles and their cluster structures covered on the surface were significantly removed, and the contour of the micron protrusions changed from a truncated cone to a quadrangular pyramid, and with the increase of the chemical treatment insulation time, the lateral size and height of the micron protrusions gradually decreased; after 30 minutes of chemical treatment, the concave area around the micron protrusions expanded to form micron pits, and shell-like structure precipitates appeared in the micron pits.
[0139] Example 4
[0140] This embodiment regulates the morphology profile of the composite pattern of micron pits and protrusions on the surface of 6061 aluminum alloy, including the following steps:
[0141] (1) The aluminum alloy sample to be processed was placed in anhydrous ethanol for ultrasonic cleaning for 10 minutes, then taken out and blown dry with dry nitrogen to remove surface contaminants.
[0142] (2) Femtosecond laser was used for surface processing, with a central wavelength of 343 nm, a pulse width of 500 fs, a pulse repetition frequency of 330 kHz, and an area of 3 × 3 mm2 for the aluminum alloy sample used. 2 , thickness is 0.22mm.
[0143] The parameters used for femtosecond laser processing are: average power 14W, scanning speed 500mm / s, and scanning times 15 times. The laser processing path is a 60° close-packed array with a single ring as a unit, the ring diameter is 43μm, and the edge spacing of adjacent concentric ring units is 30μm. The schematic diagram of the processing path is shown in Figure 7(a).
[0144] Figure 7(b) is a scanning electron microscope image of the micro-nanostructure obtained on the surface of the aluminum alloy after femtosecond laser irradiation. As shown in the figure, the composite structure obtained after femtosecond laser irradiation is a regular array of micron pits and their internal micron protrusions. The outline of the micron pits is an irregular rounded rectangle, the lateral size of the micron pits is about 45-48μm, the outline of the micron protrusions is a truncated cone, the lateral size of the micron protrusions is about 20-25μm, the depth of the micron pits and the height of the micron protrusions are about 40μm, and the spacing between the micron pits is about 30μm; the micron pits are densely covered with nanoparticles and their cluster structures, with a size of about 500nm-3μm; in addition, microcracks or micro-gap features can be seen on the edges of the micron pits, and the pit edges are relatively rough.
[0145] (3) Prepare three 50 ml portions of a mixed solution of sodium hydroxide and sodium aluminate with a molar concentration of 30 mol / L each in a beaker, place the samples processed by laser in step (2) into the three beakers containing the mixed solution, and then place the beakers in a heating furnace with the heating temperature set to 50° C. The insulation time of the three beakers is set to 30 min, 50 min, and 70 min, respectively.
[0146] (4) The sample obtained by the chemical treatment in step (3) is placed in anhydrous ethanol and ultrasonically cleaned for 10 minutes, then taken out and naturally dried at room temperature.
[0147] Figure 7(c) to Figure 7(e) The figures show scanning electron microscope images of the micron pit / protrusion composite structure obtained by femtosecond laser processing in step (2) after chemical treatment for 30 minutes, 50 minutes and 70 minutes in step (3) and ultrasonic cleaning in step (4). As can be seen from the figure, after the micron pit / protrusion composite structure obtained by femtosecond laser processing is chemically treated for 30 minutes, the nanoparticles and their cluster structures around the micron pits are significantly removed, and the microcracks or micro-gap features on the edge and inner wall of the micron pit disappear, the edge of the micron pit becomes sharper and smoother, and the outline of the micron pit becomes clearer. With the increase of chemical treatment insulation time, the micron pits gradually expanded, and the outline of the micron pits gradually transitioned from an irregular rounded rectangle before chemical treatment to a perfect circle; after 70 minutes of chemical treatment, the lateral size of the micron pits increased to about 67-70μm, and the pit spacing decreased to about 3-6μm; with the increase of chemical treatment insulation time, the height and lateral size of the micron protrusions in the pits gradually decreased. After 70 minutes of chemical treatment, the micron protrusions basically disappeared, and the structural form of the sample surface became a regularly arranged nearly perfect circular micron pit array.
[0148] Example 5
[0149] The ring spacing in step (2) of Example 4 was adjusted to 10 μm, and the other conditions were consistent with those of Example 4. The processing results were as follows:
[0150] Figure 8(a) is a scanning electron microscope image of the micro-nanostructure obtained on the surface of the aluminum alloy after femtosecond laser irradiation. It can be seen from the figure that the regular array of composite structures formed by the combination of micron pits and micron protrusions inside the micron pits obtained after femtosecond laser irradiation is still obtained. The depth of the micron pits and the height and lateral size of the micron protrusions are the same as those in Example 4, and the spacing between the micron pits becomes about 10μm; the micron pits are densely covered with nanoparticles and their cluster structures, with a size of about 500nm to 3μm; in addition, microcracks or microgap-like features can be seen on the edges of the micron pits, and the pit edges are relatively rough.
[0151] Figure 8(b) to Figure 8(d) Shown are scanning electron microscope images of the micron pit / protrusion composite structure obtained by femtosecond laser processing in step (2) after chemical treatment for 30 minutes, 50 minutes and 70 minutes in step (3) and ultrasonic cleaning in step (4). As can be seen from the figure, after 30 minutes of chemical treatment, the contour of the micron pit / protrusion composite structure obtained by femtosecond laser processing changes from an irregular rounded rectangle before treatment to a nearly perfect circle, and the lateral size of the micron pit is about 50-53μm. The micron protrusion in the pit changes from a truncated cone before treatment to a cone. At the same time, the microcracks or micro-gap features on the edge and inner wall of the micron pit disappear, the edge of the micron pit becomes sharper and smoother, and the contour of the micron pit becomes clearer. As the chemical treatment insulation time continues to increase, the micron pits gradually achieve close interconnection, and begin to transition from a circle to a hexagonal honeycomb. The lateral size and height of the micron protrusions gradually decrease. The inner wall of the micron pit and the bottom of the outer side of the micron protrusion both show shell-like structural characteristics produced by the accumulation of precipitates. The thickness of the shell-like structure precipitates is about 1-3μm. After 70 minutes of chemical treatment, the micron protrusions basically disappear, and the structural form of the sample surface becomes a regularly arranged hexagonal honeycomb array of micron pits.
[0152] Example 6
[0153] This embodiment regulates the profile of micron pits with gradient spacing on the surface of 6061 aluminum alloy, including the following steps:
[0154] (1) The aluminum alloy sample to be processed was placed in anhydrous ethanol for ultrasonic cleaning for 10 minutes, then taken out and blown dry with dry nitrogen to remove surface contaminants.
[0155] (2) Femtosecond laser was used for surface processing, with a central wavelength of 343 nm, a pulse width of 500 fs, a pulse repetition frequency of 330 kHz, and an area of 3 × 3 mm2 for the aluminum alloy sample used. 2 , thickness is 0.22mm.
[0156] The parameters used for femtosecond laser processing are: average power 15W, scanning speed 500mm / s, and scanning times 15 times. The laser processing path is a 60° close-packed array with three concentric rings as units. The diameters of the concentric rings from the outside to the inside are 50μm, 35μm, and 15μm, respectively. The edge spacing of adjacent concentric ring units increases by 10μm to achieve a spacing gradient change, ranging from 10 to 70μm. The schematic diagram of the processing path is shown in Figure 9(a).
[0157] Figure 9(b) is a scanning electron microscope image of the micro-nanostructure obtained on the surface of the aluminum alloy after femtosecond laser irradiation. As shown in the figure, the micron pit structure with gradient spacing is obtained after femtosecond laser irradiation. The outline of the micron pit is an irregular ellipse, the lateral size of the micron pit is about 45-48μm, the depth is about 40μm, and the pit spacing is 10-70μm. The micron pits are densely covered with nanoparticles and their cluster structures, with a size of about 500nm to 3μm.
[0158] (3) Use a beaker to prepare 1 portion of 50 ml of a mixed solution of sodium hydroxide and sodium aluminate with a molar concentration of 30 mol / L, place the sample obtained by laser processing in step (2) into the beaker containing the mixed solution, and then place the beaker in a heating furnace, set the heating temperature to 50°C, and set the insulation time to 60 min. After the insulation is completed, take out the sample and place it in anhydrous ethanol for ultrasonic cleaning for 10 min. Then, place the sample again in a newly prepared portion of 50 ml of a mixed solution of sodium hydroxide and sodium aluminate with a molar concentration of 30 mol / L, and place the beaker in a heating furnace, set the heating temperature to 60°C, and set the insulation time to 40 min.
[0159] (4) The sample obtained by the chemical treatment in step (3) is placed in anhydrous ethanol and ultrasonically cleaned for 10 minutes, then taken out and naturally dried at room temperature.
[0160] FIG9(c) shows a scanning electron microscope image of the micron pit structure with a gradient spacing obtained by femtosecond laser processing in step (2), after two consecutive chemical treatments in step (3) and ultrasonic cleaning in step (4). As can be seen from the figure, after two consecutive chemical treatments, the originally irregularly shaped micron pits eventually become a hexagonal honeycomb structure; due to the different spacings of the micron pits in different parts, the pits can expand to different ranges during the chemical treatment, so the final result is a hexagonal honeycomb structure with a gradient size variation, and the honeycomb side length is 30 to 65 μm.
[0161] Example 7
[0162] This embodiment regulates the profile of micron pits with gradient diameter changes on the surface of 6061 aluminum alloy, including the following steps:
[0163] (1) The aluminum alloy sample to be processed was placed in anhydrous ethanol for ultrasonic cleaning for 10 minutes, then taken out and blown dry with dry nitrogen to remove surface contaminants.
[0164] (2) Femtosecond laser was used for surface processing, with a central wavelength of 343 nm, a pulse width of 500 fs, a pulse repetition frequency of 330 kHz, and an area of 3 × 3 mm2 for the aluminum alloy sample used. 2 , thickness is 0.22mm.
[0165] The parameters used for femtosecond laser processing are: average power 15W, scanning speed 500mm / s, and scanning times 15 times. The laser processing path is a 90° array with multiple concentric rings as units. The innermost circle diameter of the concentric ring unit is 20μm, and then the diameter of the ring increases by 10μm, and the diameter of the outermost circle increases by 10μm to achieve a gradient change, ranging from 50 to 130μm. The edge intervals of adjacent concentric ring units are all 20μm. The schematic diagram of the processing path is shown in Figure 10(a).
[0166] Figure 10(b) is a scanning electron microscope image of the micro-nanostructure obtained on the aluminum alloy surface after femtosecond laser irradiation. As shown in the figure, the micron pit structure with a gradient diameter is obtained after femtosecond laser irradiation. The outline of the micron pit is an irregular ellipse. Some unablated convex structures appear inside the micron pit with a larger diameter. The lateral size of the micron pit is about 50 to 130 μm, the depth is about 40 μm, and the pit spacing is 20 μm. The micron pit is densely covered with nanoparticles and their cluster structures, with a size of about 500 nm to 3 μm.
[0167] (3) Prepare a 50 ml portion of a mixed solution of sodium hydroxide and sodium aluminate with a molar concentration of 30 mol / L in a beaker, place the sample obtained by laser processing in step (2) in the beaker containing the mixed solution, and then place the beaker in a heating furnace, set the heating temperature to 50°C, and set the insulation time to 60 min. After the insulation is completed, take out the sample and place it in anhydrous ethanol for ultrasonic cleaning for 10 min. Then, place the sample again in a newly prepared 50 ml portion of a mixed solution of sodium hydroxide and sodium aluminate with a molar concentration of 30 mol / L, and place the beaker in a heating furnace, set the heating temperature to 60°C, and set the insulation time to 40 min.
[0168] (4) The sample obtained by the chemical treatment in step (3) is placed in anhydrous ethanol and ultrasonically cleaned for 10 minutes, then taken out and naturally dried at room temperature.
[0169] FIG10(c) shows a scanning electron microscope image of the micron pit structure with a diameter gradient obtained by femtosecond laser processing in step (2), after two consecutive chemical treatments in step (3) and ultrasonic cleaning in step (4). As can be seen from the figure, after two consecutive chemical treatments, the originally irregular micron pits have become more regular, close to a perfect circle, and in close contact with each other; the convex structure inside the large-diameter pits caused by insufficient laser ablation is gradually removed during the chemical treatment; in addition, since the micron pits are arranged in a 90° array, the pits do not form a hexagonal honeycomb structure after chemical treatment, but form a quadrilateral grid structure with a size gradient, and the quadrilateral side length is 60 to 150 μm.
[0170] In the description of the present invention, it should be understood that the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Thus, a feature defined as "first" or "second" may explicitly or implicitly include at least one of the features. In the description of the present invention, the meaning of "plurality" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined.
[0171] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0172] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.
Claims
1. A metal surface patterning micro-nano processing method, characterized in that: include: irradiating the surface of the metal part with an ultrafast laser according to a predetermined path to form a first micro-nano structure on the surface of the metal part; Using a chemical reagent to chemically treat the surface of the metal part having the first micro-nano structure formed thereon, so that the first micro-nano structure changes and a second micro-nano structure is formed on the surface of the metal part; The surface of the metal part that has undergone the chemical treatment is cleaned to obtain a metal part having a micro-nano structure on the surface.
2. The metal surface patterning micro-nano processing method according to claim 1, characterized in that: The metal part meets at least one of the following conditions: The metal parts include at least one of gold, silver, platinum, aluminum and aluminum alloys, magnesium and magnesium alloys, zinc and zinc alloys, copper and copper alloys, titanium and titanium alloys, tungsten and tungsten alloys, nickel and nickel alloys, manganese and manganese alloys, iron, and steel; The metal piece may be in the form of at least one of a metal block, a metal foil, a metal mesh, and a metal foam.
3. The metal surface patterning micro-nano processing method according to claim 1, characterized in that: The ultrafast laser satisfies at least one of the following conditions: The ultrafast laser is at least one of ultraviolet, infrared and visible light; The wavelength of the ultrafast laser is 100nm to 2000nm; The pulse width of the ultrafast laser is 1fs to 30ps; The pulse frequency of the ultrafast laser is 1 Hz to 1 GHz; The average power of the ultrafast laser is 1 mW to 10 kW.
4. The metal surface patterning micro-nano processing method according to claim 1, characterized in that: The predetermined path includes at least one of a point, a parallel line, a cross line, a ring, a concentric circle, a spiral line, a zigzag line and a free pattern.
5. The metal surface patterning micro-nano processing method according to claim 1, characterized in that: The first micro-nano structure includes a first micron structure and a first nano structure located on the first micron structure; The first nanostructure includes at least one of nanoparticles, nanoripples, nanohairs, nanosynapses and nanoparticle clusters; The first microstructure satisfies at least one of the following conditions: The first micron structure includes at least one of a first micron protrusion, a first micron pit, and a combination thereof; The shape of the first micron protrusion includes at least one of a conical shape, a truncated cone shape, a cylindrical shape, a square cone shape and an irregular shape protrusion; The lateral size of the first micron protrusion is 0.1 μm to 1000 μm; The shape of the first micron pits includes at least one of a circular, oval, square, polygonal, groove-shaped and irregular-shaped holes; The lateral size of the first micron pit is 0.1 μm to 1000 μm.
6. The metal surface patterning micro-nano processing method according to claim 1, characterized in that: The chemical treatment satisfies at least one of the following conditions: The chemical reagent includes at least one of an acid, a base, a salt and a mixed solution thereof; The temperature of the chemical treatment is -100°C to 300°C; The time of the chemical treatment is 1 second to 120 hours.
7. The metal surface patterning micro-nano processing method according to claim 5, characterized in that: The change in the first micro-nano structure includes at least one of the following: 1) The first nanostructure is removed, and the surface of the first microstructure becomes smoother; 2) The micro cracks or micro gaps at the edge of the first micron pit profile are removed, and the edge of the first micron pit profile is clearer; 3) The first micron protrusion gradually disappears; 4) the profile of the first micron pit gradually expands and the depth of the first micron pit gradually increases; 5) The shape of the first micron pit changes; 6) Precipitates appear on the surface of the first micron protrusions or the first micron pits.
8. The metal surface patterning micro-nano processing method according to claim 1, characterized in that: The second micro-nano structure includes at least one of a second micron protrusion, a second micron pit, and a combination thereof; The second micro-nanostructure satisfies at least one of the following conditions: The shape of the second micron protrusions includes at least one of a conical shape, a truncated cone shape, a cylindrical shape, a square cone shape and an irregular shape protrusion; The lateral size of the second micron protrusion is 0.1 μm to 1000 μm; The shape of the second micron pits includes at least one of a circular, oval, square, polygonal, groove-shaped and irregular-shaped holes; The lateral size of the second micron pit is 0.1 μm to 1000 μm.
9. A metal part, characterized in that: At least part of the surface of the metal part has a micro-nano pattern and / or structure, and the micro-nano pattern and / or structure is prepared by the metal surface patterning micro-nano processing method according to any one of claims 1 to 8.
Citation Information
Patent Citations
Method for preparing super-hydrophobic bionic metal surface through ultrafast laser technology
CN108393588A
Timepiece dial or covering element made from non-conductive material
CN110268337A
Wettability-adjustable super-lubricity super-amphiphobic surface and oil control and preparation method thereof
CN111054610A
Patterning and removal of circuit board material using ultrafast lasers
US20200008305A1